2018
DOI: 10.3390/microorganisms6020052
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Elicitors of Antibiotic Biosynthesis in Actinomycetes

Abstract: Whole genome sequencing of actinomycetes has uncovered a new immense realm of microbial chemistry and biology. Most biosynthetic gene clusters present in genomes were found to remain “silent” under standard cultivation conditions. Some small molecules—chemical elicitors—can be used to induce the biosynthesis of antibiotics in actinobacteria and to expand the chemical diversity of secondary metabolites. Here, we outline a brief account of the basic principles of the search for regulators of this type and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 64 publications
(66 reference statements)
0
27
0
Order By: Relevance
“…Later, from the fermentation broth of Saccharothrix algeriensis NRRL B-24137 (fully sequenced strain) isolated from a Saharan soil sample collected in 1992 at a palm grove in Adrar (southwest of Algeria), Merrouche et al [82,83] isolated the new dithiolopyrrolone derivatives valerylpyrrothine (6), isovalerylpyrrothine (7), and formylpyrrothine (8) by addition of valeric acid to the culture medium and the known aureothricin (9), exhibiting a moderate bioactivity against some filamentous fungi and yeasts such as Mucor ramanniamus, Penicillium expansum, and Aspergillus carbonarius. Moreover, the new crotonyl-pyrrothine (10), sorbyl-pyrrothine (11), 2-hexonyl-pyrrothine (12), and 2-methyl-3-pentenyl-pyrrothine (13) were obtained by addition of sorbic acid to the culture medium. Compound 11 resulted in the most active in the series against Gram-positive bacteria.…”
Section: Antimicrobialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, from the fermentation broth of Saccharothrix algeriensis NRRL B-24137 (fully sequenced strain) isolated from a Saharan soil sample collected in 1992 at a palm grove in Adrar (southwest of Algeria), Merrouche et al [82,83] isolated the new dithiolopyrrolone derivatives valerylpyrrothine (6), isovalerylpyrrothine (7), and formylpyrrothine (8) by addition of valeric acid to the culture medium and the known aureothricin (9), exhibiting a moderate bioactivity against some filamentous fungi and yeasts such as Mucor ramanniamus, Penicillium expansum, and Aspergillus carbonarius. Moreover, the new crotonyl-pyrrothine (10), sorbyl-pyrrothine (11), 2-hexonyl-pyrrothine (12), and 2-methyl-3-pentenyl-pyrrothine (13) were obtained by addition of sorbic acid to the culture medium. Compound 11 resulted in the most active in the series against Gram-positive bacteria.…”
Section: Antimicrobialsmentioning
confidence: 99%
“…Compound 47 emerged as the most active in the series, mainly on Gram-positive bacteria and fungi (MICs in the range 1-50 µg/mL corresponding to 4.6-230 µM). [24,81] Valerylpyrrothine (6), Isovalerylpyrrothine (7), Formylpyrrothine (8), Aureothricin (9) antibacterial and antifungal Saccharothrix algeriensis NRRL B-24137, fully sequenced strain Saharan soil [82] Crotonyl-pyrrothine (10), Sorbyl-pyrrothine (11), 2-Hexenyl-pyrrothine (12), 2-Methyl-3-pentenyl-pyrrothine (13) antibacterial and antifungal Saccharothrix algeriensis NRRL B-24137 Saharan soil [83] Benzoyl-pyrrothine dithiolopyrrolone (14) antibacterial, antifungal Saccharothrix algeriensis NRRL B-24137 palm grove soil (Southern Algeria) [84] Mutactimycin PR (15) Toumatia et al [110] and, recently, Djinni et al [111] isolated novel strains producing actinomycin D (49) and showed that genus Streptomyces isolated from Saharan soil of Ain amenas (Streptomyces sp. IA1) and Beni Abbes-Bechar (Streptomyces sp.…”
Section: Antimicrobialsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The responsible biosynthetic genes are ‘silent’ under laboratory condition and are regulated via unknown mechanisms. 5,6…”
Section: Introductionmentioning
confidence: 99%
“…The intracellular target of A-factor has been identified as a member of the TetR family, and these receptors are shown to regulate of antibiotic biosynthesis in in several actinobacterial species (Figure 1A). 69 The use of exogenous GBLs has been shown to induce secondary metabolite production from otherwise silent clusters. 10,11 However, the alkali labile nature of γ-butyrolactones, and the pleiotropic nature of GBL-mediated regulation limit the general use of these hormones.…”
Section: Introductionmentioning
confidence: 99%